2011
DOI: 10.19030/iber.v6i5.3367
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis Of International Mutual Fund Performance

Abstract: Since 1990 there has been a tremendous growth in the investment in international mutual funds. This growth is likely to continue as domestic stock market cools down and more U.S. investors seek higher returns as well as the diversification benefits of foreign assets. Investors are also attracted to international funds in the belief that such funds earn abnormally high returns because of the previous relative inefficiency in those markets. This study examines the annual risk-adjusted returns using Sharpes Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The funds were however, negatively related to systematic risk, same as in Mohammad (2013) and Surang (2022). The target had a negative impact on fund returns, signaling a better performance with international investments, similar to the findings in Rao and Aggarwal (1987), Detzler and Wiggins (1997), Boudreaux Et Al (2007). A positive association of the fund performance to faith factor, unlike in Adams & Ahmed (2012), indicates that Islamic funds rely in part on Sharia compliant investments and strategies to improve their performances.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The funds were however, negatively related to systematic risk, same as in Mohammad (2013) and Surang (2022). The target had a negative impact on fund returns, signaling a better performance with international investments, similar to the findings in Rao and Aggarwal (1987), Detzler and Wiggins (1997), Boudreaux Et Al (2007). A positive association of the fund performance to faith factor, unlike in Adams & Ahmed (2012), indicates that Islamic funds rely in part on Sharia compliant investments and strategies to improve their performances.…”
Section: Resultssupporting
confidence: 72%
“…The decision depends on the size of the market opportunity, diversification opportunities or issues, political stability, emerging versus developed markets preferences and social-cultural boundaries. Going global provides access to fastest-growing markets, even with high level of risk, as confirmed by Boudreaux et al (2007). Currency risk, however, should be appropriately hedged.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some studies find no evidence of positive abnormal returns (Cumby & Glen, 1990;Droms & Walker, 1994;Tsai & Wu, 2015) whilst others find that performance results depend on the benchmark index used for comparison (Eun, Kolodny, and Resnick, 1991). Other papers have found consistent evidence of abnormal performance (Redman, Gullet, and Manakyan, 2000;Boudreaux, Rao, Ward, and Ward, 2007) but reach different conclusions regarding performance persistence. In a study of international equity funds, Droms and Walker (2001) find statistically significant performance persistence for very short-term (1-year) holding periods only.…”
Section: Introductionmentioning
confidence: 91%
“…Another perspective on mutual funds studies was examining the performance of funds investing locally and internationally. Most studies in the U.S. found that funds invested internationally outperformed locally invested funds (Redman, Gullet, & Manakyan, 2000;Boudreaux, Uma Rao, Ward, & Ward, 2007) whereas in the U.K., evidence showed that funds invested outside of the U.K. did not produce superior performance as compared to the locally invested funds (Abel & Fletcher, 2004;Fletcher, 1999;Fletcher & Marshall, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%